2017
DOI: 10.3126/njog.v11i2.17460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Rectal Misoprostol on Blood Loss during and after Elective Cesarean Delivery: A Randomized Controlled Trial

Abstract: Aims:The aim of this study was to evaluate the effect of preoperative administration of rectal misoprostol onblood loss during and after elective cesarean delivery.Methods:It was a randomized trial including 200 women, divided into two groups (group A and group B), who were planned for elective cesarean delivery and didn’t have risk of postpartum hemorrhage (PPH). Group A received 400μg misoprostol per-rectal preoperatively and intravenous infusion of oxytocin after delivery as hospital protocol.Group B receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…However, this insignificant difference is due to estimating the blood loss based on deficit in hemoglobin level pre and postoperative as the sufficient data about number of towels used and the amount of blood in surgical suctions during cesarean delivery is lacked. This finding agrees with Sitaula S. et al (2017) who found that carbetocin was superior to misoprostol in decreasing intraoperative blood loss [20] .…”
Section: Discussionsupporting
confidence: 92%
“…However, this insignificant difference is due to estimating the blood loss based on deficit in hemoglobin level pre and postoperative as the sufficient data about number of towels used and the amount of blood in surgical suctions during cesarean delivery is lacked. This finding agrees with Sitaula S. et al (2017) who found that carbetocin was superior to misoprostol in decreasing intraoperative blood loss [20] .…”
Section: Discussionsupporting
confidence: 92%
“…Though primary prevention with oxytocin is being practiced widely, it is not always effective and the need of additional or adjuvant uterotonics is reported to be 10-40%. 9,10 The logic pertaining to the choice of adjuvant utertonic, timing, dose and route used in the present study was in accordance to recent evidence while formulating an innovative approach of using administration of adjunct misoprostol in selective group of parturient as discussed below:…”
Section: Discussionsupporting
confidence: 53%
“…The efficacy of misoprostol alone as well as an adjunct to oxytocin for prevention of PPH is well documented. [9][10][11][12][13][14][15][16][17][18][19][20] In contrast very few studies have reported a contrary view but have used a lower dose. 21 Choosing the optimal dose is imperative to achieve the goal as discussed later.…”
Section: Discussionmentioning
confidence: 99%